Pembuatan Item Pertanyaan Mata Pelajaran Ekonomi SMA Kelas XI Mengacu pada Kurikulum Merdeka - Mulyati, Budi; Nurlaili, Fitri; Susilawati, Yayu (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2024)
This study aimed to analyze the question items of Economics subjects classically in order to develop question items for summative assessment, which refers to Kurikulum Merdeka. This research used development research which refers to the development research design from Sugiyono. The results showed that the question items produced had a range of varying levels of difficulty, difficult 49%, medium 30% and easy 21%. The discrimination index possessed by a set of items made was good as general, this was indicated by the proportion of discrimination index of most items or 66% usable, although the other 18 items of the question of 34% must be revised. The distractors in the items that have been created most or 74.3% are accepted, the rest others require revision and replacement.